2017
DOI: 10.1080/21640629.2017.1367068
|View full text |Cite
|
Sign up to set email alerts
|

Emotions, identity, and power in video-based feedback sessions: tales from women’s professional football

Abstract: While video-based feedback has become an increasingly salient feature of practice in high performance sport, it has received relatively little attention in the coaching literature. Data for this study were generated through a process of collaborative critical reflection and cyclical, in-depth interviews with elite female footballers. Using fictional narratives as a mode of representation, we highlight the emotional, embodied, and relational features of two athletes' experiences of video-based feedback. Burkitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Specifically, they believe that people have been largely presented as variables; be they dependent variables (that experience certain outcomes), independent variables (that possess certain qualities or attributes), or intervening variables (people act as a medium through which structures exert influence or produce particular outcomes; Grills & Prus, 2019). Importantly, they argued that such work loses sight of human agency and the iterative and interactive making of everyday management work in-situ (Grills & Prus, 2019;Magill, Nelson, Jones & Potrac, 2017). Indeed, for them, joint and co-ordinated action "is not some neutral medium through which structural variables pass to produce some predicted and predictable outcome" (Grills & Prus, 2019, p. 6).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Specifically, they believe that people have been largely presented as variables; be they dependent variables (that experience certain outcomes), independent variables (that possess certain qualities or attributes), or intervening variables (people act as a medium through which structures exert influence or produce particular outcomes; Grills & Prus, 2019). Importantly, they argued that such work loses sight of human agency and the iterative and interactive making of everyday management work in-situ (Grills & Prus, 2019;Magill, Nelson, Jones & Potrac, 2017). Indeed, for them, joint and co-ordinated action "is not some neutral medium through which structural variables pass to produce some predicted and predictable outcome" (Grills & Prus, 2019, p. 6).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Athletes will not have the same reaction to RPE data as the coach. For example, an athlete's emotional state and position in the organization will heavily influence how they engage with and react to the dissemination of data that considers their physiological profile or performance output (31). In addition, although the perceived performance benefits of constant surveillance may seem evident, socio-culturally informed research has indicated that the corresponding imposition of discipline as a result of monitoring approaches may well have an adverse effect on an athlete's engagement with their athletic role (41).…”
Section: Reading Load Monitoring and Rating Of Perceived Exertion Wit...mentioning
confidence: 99%
“…It is here that sport psychology research may benefit from adopting a similar focus on the dynamic and frequently contested nature of inter-personal relations to that which has been adopted in the sports coaching literature (e.g. Jones & Wallace, 2005;Magill, Nelson, Jones, & Potrac, 2017;Potrac, Mallett, Greenough, & Nelson, 2017).…”
Section: Introductionmentioning
confidence: 99%